Les micro-récits de Delerm pour un nourrissage culturel effectif en classe de FLE - Martinez, Christine (Neofilolog, 2022)
The article proposes to study the impact of Delerm’s micro-stories in the FL classroom from a cultural perspective. These literary materials create opportunities for spontaneous dialogue and sharing that enrich the individual and common cultural reservoir and lexical repertoire of the learners. This study shows that micro-stories are significantly easier to introduce into the academic curriculum than whole books, without too much effort on the part of the teacher and the learner, but with a very satisfactory result for both sides. A focused definition of the term culture is presented at the beginning to set the framework for the study. This is followed by Delerm’s literalism, i.e., we tried to hone the learn- ers’ skills in reading and understanding a simple text so they would be able to (re)use the acquired information in academic, professional, or personal life. Then, the exploitation of micro-stories in the FL classroom is presented with multiple explanations and, finally, our concluding re- marks close this contribution.